2010
DOI: 10.1007/s12208-010-0053-6
|View full text |Cite
|
Sign up to set email alerts
|

Consumer behavioural intentions in cause-related marketing. The role of identification and social cause involvement

Abstract: The main purpose of this research is to analyze the role of consumer identification with the company and consumer involvement with the social cause in consumer behavioural responses to Cause-related Marketing. A theoretical model was empirically estimated based on data taken from 595 consumers of insurance and personal hygiene products and using structural equation modelling. A multigroup analysis was performed in order to test the moderating effect of consumer involvement with the social cause. Findings confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 59 publications
2
34
0
Order By: Relevance
“…Furthermore, the framework shows that there may be a lot of space between functional fit and image fit, as previously distinguished by Bigné Alcañiz et al (2010) and Bigné et al (2012). Products and services is the category that connects best to the original concept of functional fit.…”
Section: Discussion Main Findingsmentioning
confidence: 69%
See 4 more Smart Citations
“…Furthermore, the framework shows that there may be a lot of space between functional fit and image fit, as previously distinguished by Bigné Alcañiz et al (2010) and Bigné et al (2012). Products and services is the category that connects best to the original concept of functional fit.…”
Section: Discussion Main Findingsmentioning
confidence: 69%
“…Ailawadi et al (2014), for instance, showed that the effects of CSR activities varied between the four CSR domains they distinguished, and Grau and Folse (2007) found that local donations, as opposed to national ones, had a positive effect on cause-related marketing outcomes. Likewise, Bigné-Alcañiz et al (2010) found that consumers' social cause involvement moderated the relationship between their consumer-company identification and their behavioral intentions. The costs involved for the stakeholders are another important aspect: Andrews et al (2014) showed that price discounts moderated the effects of cause-related marketing campaigns, while Folse et al (2010) found that purchase quantity affected consumers' participation intentions.…”
Section: Key Factors In Achieving Positive Csr Outcomesmentioning
confidence: 96%
See 3 more Smart Citations